2020
DOI: 10.1371/journal.pone.0237891
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pterygium and its associated factors among adults aged 18 years and above in Gambella town, Southwest Ethiopia, May 2019

Abstract: Introduction A pterygium is a wing-shaped fibro-vascular growth of conjunctiva on the superficial cornea/ conjunctiva. It is an elastotic degeneration of conjunctival stroma mainly due to Ultraviolet light exposure. The prevalence of pterygium varies in different environmental conditions. Its magnitude varies widely from 1.1% to 53% globally and in Ethiopia, it reaches from 8.8% to 38.7%. Objective To determine the prevalence of pterygium and its associated factors among adults aged 18 years and above in Gambe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
3
8
0
1
Order By: Relevance
“…This finding is in contrast to the studies in [8,9], whereby the authors concluded that systemic factors will not induce the pterygium condition. Besides the above, another study [13] from Gambella, Ethiopia agreed with the previously observed major risk factors, such as exposure to sunlight and outdoor activities. However, they also found that males have greater risk of being affected by pterygium compared to females, which supports the findings of Cahjucom-Uy et al [12].…”
Section: Pterygium Risk Factorssupporting
confidence: 87%
“…This finding is in contrast to the studies in [8,9], whereby the authors concluded that systemic factors will not induce the pterygium condition. Besides the above, another study [13] from Gambella, Ethiopia agreed with the previously observed major risk factors, such as exposure to sunlight and outdoor activities. However, they also found that males have greater risk of being affected by pterygium compared to females, which supports the findings of Cahjucom-Uy et al [12].…”
Section: Pterygium Risk Factorssupporting
confidence: 87%
“…4 Dilihat dari prevalensi yang bervariasi berdasarkan karakteristik pada derah Jawa Barat cukup banyak kejadian pterygium dan tingginya jumlah kunjungan pasien di RSUD Al Ihsan pada layanan kesehatan mata, tetapi data penelitian tersebut belum menjelaskan data terkait dengan gambaran karakteristik pterygium di RSUD Al Ihsan.Oleh karena itu maka dilakukan penelitian untuk mengetahui gambaran karakteristik pterygium pada pasien di RSUD Al Ihsan pada tahun 2016-2021. [1] Berdasarkan latar belakang yang telah diuraikan, maka perumusan masalah dalam penelitian ini sebagai berikut: "Bagaimana gambaran karakteristik pterygium pada pasien di RSUD Al Ihsan pada tahun 2016-2021?". Selanjutnya, tujuan dalam penelitian ini diuraikan dalam pokok-pokok sbb.…”
Section: Aunclassified
“…8 In addition to cosmetic problems, pterygium can lead to eye irritation, disrupt the transparency of the pupil area, and cause disorders such as corneal astigmatism; in addition, it may rarely lead to visual impairment due to damage to the visual axis, which in severe cases requires surgery. 6,[9][10][11] Due to the importance of this disease, this review provides a major review on etiologies, risk factors, complications, and surgical management of pterygium, focusing on the updates and the new features of the literature. Since new methods and medications are constantly developed to further reduce the recurrence of the pterygium after excision, different methods of pterygium surgery and recent adjuvant therapies are discussed in this review article.…”
Section: Introductionmentioning
confidence: 99%